How to wire rural India: problems and possibilities of digital development - Sood, Aditya Dev (2001)
Digital development affords a new perspective from which to imagine the future directions of India's political economy. Rather than remaining locked in the paradigm of an eternally developing it now seems possible to aspire to becoming acknowledge society. This article critically examines the problems and possibilities of digital development in order to reveal the larger impact that information and communication technologies could have on rural economies and societies. - Reproduced
Keywords: Rural development - India; Information technology - India; Communication technology - India; Information technology; Communication technology